Re-examining the factors that heighten students' motivation to write - Caturay, Warlito S. Jr. (2009)
This paper looks at ESL university students' attitudes towards the factors that may heighten their motivation to write and their teachers' perceptions of students' attitudes towards writing, the teachers, as well as their classroom materials and activities, and their assessment process. Also, this paper attempted to find out what strategies teachers use to increase students' interest to write.
The data gathered showed that students generally have positive attitudes towards writing. They know the importance of writing in their lives and its values. Students also showed positive attitudes towards their teachers, the materials used in class, the activities in the classroom and the assessment process. It also revealed that teachers judiciously and consciously choose classroom materials, activities, and assessment strategies to increase students' motivation.
Keywords: Writing processes; Penmanship